PENGARUH SISTEM INFORMASI KEPEGAWAIAN DAN PENDIDIKAN DAN PELATIHAN TERHADAP LAYANAN KENAIKAN PANGKAT PNS (Studi Kasus pada BKD Pemerintah Propinsi Kalimantan Selatan) - Muhammad Umar Hamdan; Rahmi Widyanti (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to: (1) Investigate and assess the impact of the Personnel Information System on public servant advancement services at the Regional Personnel Agency of the South Kalimantan Provincial Government. (2) Investigate and assess the impact of Education and Training on the promotion services of public servants at the Regional Personnel Agency of the South Kalimantan Provincial Government. (3) Investigate and assess the concurrent impact of the Personnel Information System and Education & Training on public servant advancement services at the Regional Personnel Agency of the South Kalimantan Provincial Government.This study was carried out at the Regional Personnel Agency of the South Kalimantan Provincial Government. The used methodology is descriptive quantitative. This study's population comprises public servants and non-permanent workers of the Regional Personnel Agency of the South Kalimantan Provincial Government. The sample included 48 respondents chosen by purposive sampling, with data collection conducted using surveys and questionnaires. Data analysis methodologies used SPSS Version 25. The Personnel Information System has a favourable and substantial impact on civil servant advancement services at the Regional Personnel Agency of the South Kalimantan Provincial Government. Education and training have a favourable and substantial influence on the promotion services for public servants at the Regional Personnel Agency of the South Kalimantan Provincial Government. The Personnel Information System and Education & Training concurrently have a substantial impact on civil servant advancement services at the Regional Personnel Agency of the South Kalimantan Provincial Government.This study concludes that the Personnel Information System and Education & Training each exert a positive and significant partial influence on civil servant promotion services. Furthermore, both the Personnel Information System and Education & Training collectively have a significant impact on civil servant promotion services at the Regional Personnel Agency of the South Kalimantan Provincial Government.